Estudio del movimiento del punto ETCG con base en mediciones GPS y dentro del sistema mundial ITRF (ING) - Moya Zamora, Jorge (2002)
The variation of the elipsoidic position of the ETCG point was determined using two differents epochs of GPS measurements, after its first tieing to The International Terrestrial Reference Frame (ITRF) in 1998. As a product of this tie, the ETCG position was obtained with high accuracy, with errors in the adjusted coordinates on the order centimeter, wich leaves open the possibility to make new measurements and to study the motion that happens in that particular point whit high accuracy. In this investigation, two types of new links were made to the world system, by means of differential GPS measurements, one made in mid 1999, and the other, at the end of the year 2000. The results show that within the period selected, an three-dimensional motion existed in the ETCG point, however considering only the coordinates of latitude and longitude, the resultant motion was not statistically significant.